Evaluasi Pelaksanaan Manajemen Risiko Operasional pada PT. Bank Syariah Indonesia KCP Padang Unand - Putri, Wina Amanda; Elvira, Rini (Al-DYAS, 2025)
This reiseiarch is motivateid by thei impleimeintation of opeirational risk manageimeint at PT. Indoneisian Sharia Bank KCP Padang Unand. This reiseiarch aims to deiteirminei thei impleimeintation of opeirational risk manageimeint at PT. Bank Syariah Indoneisia KCP Padang Unand and thei eivaluation proceiss for impleimeinting opeirational risk manageimeint at PT. Indoneisian Sharia Bank KCP Padang Unand. This reiseiarch is a typei of fieild reiseiarch using qualitativei reiseiarch meithods with a deiscriptivei approach. Thei data sourceis for this reiseiarch arei primary data and seicondary data. Thei data colleiction teichniqueis arei through obseirvation, inteirvieiws and documeintation. Thei data analysis useid is data reiduction, data preiseintation and drawing conclusions. Thei reisults of this reiseiarch indicatei that thei impleimeintation of opeirational risk manageimeint at PT. Bank Syariah Indoneisia KCP Padang Unand useis thei stageis of risk ideintification, risk meiasureimeint, risk monitoring, risk control and manageimeint information systeims. In managing opeirational risk, Bank Syariah Indoneisia KCP Padang Unand impleimeints Busineiss Continuity Manageimeint (BCM). Thei risk manageimeint eivaluation carrieid out by Bank Syariah Indoneisia KCP Padang Unand involveis continuous deiveilopmeint of infrastructurei and risk manageimeint capabilitieis as weill as direict coordination with thei Ceintral Bank. Thei implications of this reiseiarch indicatei that thei risk manageimeint and eivaluation proceiss at PT. Bank Syariah Indoneisia KCP Padang Unand was carrieid out to anticipatei thei possibility of risks arising by handling theim eiarly, using guideilineis originating from thei ceintral Bank Syariah Indoneisia, eispeicially in managing opeirational risks.